'The state of the debate': A media analysis of the debates on liberalization and citizenship education in France, Sweden, and England, 2001–2010. (July 2013) - Côté, Isabelle; Sundström, Malena Rosén; Sannerstedt, Anders
Over the last decades, many liberal democracies have experienced a tension between the education system's expressed requirement to foster citizenship norms and the liberal (sub-)ideal of norm neutrality. This dilemma has been accentuated by, on the one hand, increased ethnical and cultural diversity and, on the other hand, liberalization of society in general and the schooling system in particular. This article provides a 'state of the debate' of this tension in France, Sweden, and England, through a media analysis of the period 2001–2010. Citizenship education was most prominent in the Swedish debate. The Swedish and English positions were most alike, arguing for 'objective civics' and promoting freedom of choice in the school system. In contrast, the French debate argued for a common, integrative state-managed school system that provides equal opportunities to all socioeconomic groups while inculcating loyalty to the State.